Using association rule mining to identify risk factors for early childhood caries. Issue 2 (November 2015) - Ivančević, Vladimir; Tušek, Ivan; Tušek, Jasmina; Knežević, Marko; Elheshk, Salaheddin; Luković, Ivan
Highlights We look for an approach to massive risk factor discovery for early childhood caries. Association rule mining with adequate rule pruning and ranking performs well. Literature supports most risk factors identified in associative analysis. When coupled with other risk factors frequent breastfeeding confirmed as a risk. Parent health awareness significant only for boys.